Formulación del plan estratégico para la empresa Krear Tech Mayorista para los años 2022-2024 (2021)
KREAR TECH WHOLESALE, is an organization located in the medium business sector, its main activities are buying and selling, accessories, maintenance, repairs, consulting and among others, in the technology market it has been in the city of Cali for more than 15 years